Deixis Analysis of the Good Dinosaur theMovie - Nur Kholis (IAIN Salatiga, 2016)
This essay is a descriptive qualitative research which will attempt to answer the following objectives: (1) what are types of deixis found in the movie of “The Good Dinosaur”? And (2) what is the most dominant deixis found in the movie “The Good Dinosaur” and the analysis?From the analysis of the movie entitled “The Good Dinosaur”, found some data finding about the types of deixis which used in the movie. Five types of deixis they are: personal deixis, time deixis, place deixis, social deixis, and discourse deixis found in the film in the different data percentage. Personal deixis found in the highest percentage which directly answers the second objective with the data collection 80%, time deixis 5%, place deixis 3%, social deixis 9% and discourse deixis 3%.Personal deixis has a correlation to the point of view of narrating the film “The Good Dinosaur”. This caused by the finding of personal deixis involving thr first, second and third pronoun in determining the story. Further, this contribute to make the personal deixis dominate the deixis used in the film.